The Comparative study of the effect of ethical valuation different criteria on economic policy making and its implications for Islamic economics - seyed mohammad ali mousavi; mohammad javad tavakoli (روش شناسی علوم انسانی, 2020)
Although economists typically try to make their theories free from ethical evaluations, their theories are value laden. In this paper, we examine the impact of ethical schools on economic policies. The findings of the paper show that consequential, deontological, virtue-based and rights-based ethics have a particular impact on economic policy making. These approaches, while affecting the definition of the goals of economic policies, provide the basis for establishing the principles that define the framework of economic policies for achieving those goals. The result of this trend is that neoclassical utilitarian economists, with an emphasis on the role of complete competition market for achieving welfare, propose price policies to compensate market failure. The policy orientation in the capability-based approach of Sen and rights-based Contractarianism of Rawls, through the creation of changes in the structure of the market and the introduction of new institutions, is respectively, human development and the provision of basic goods to the poorest of the community. The feminist virtue-based economists also propose the promotion of the role of women's caring activities in their policy orientations.